2007 IEEE Particle Accelerator Conference (PAC) 2007
DOI: 10.1109/pac.2007.4440698
|View full text |Cite
|
Sign up to set email alerts
|

Progress towards a gap free dielectric-loaded accelerator

Abstract: One of the major concerns in the development of Dielectric-Loaded Accelerating (DLA) structures is the destructive breakdown at dielectric joints caused by a local electric field enhancement induced by the discontinuity of the dielectric constant at the surface of the joint gap. Our previous X-band traveling wave DLA structure design [1], for example, incorporated two separate impedance matching sections with at least two dielectric joints. In this paper, we present a new design to avoid this problem. This sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…According to the preceding studies of DLA structures, a dielectric joint breakdown occurred at microgaps [27] and rf power absorption caused by single-surface multipactor was experimentally found [28,29]. Therefore, in order to realize a high-gradient DAA structure, it is essential to develop a careful design of input coupler and dielectric cell assembly to avoid the rf breakdown and to mitigate multipactoring.…”
Section: Discussionmentioning
confidence: 99%
“…According to the preceding studies of DLA structures, a dielectric joint breakdown occurred at microgaps [27] and rf power absorption caused by single-surface multipactor was experimentally found [28,29]. Therefore, in order to realize a high-gradient DAA structure, it is essential to develop a careful design of input coupler and dielectric cell assembly to avoid the rf breakdown and to mitigate multipactoring.…”
Section: Discussionmentioning
confidence: 99%
“…It is revealed in [16,17] that integration of the dielectric parts of the coupler and tube can prevent the RF breakdown occurred because of the air gap that existed at the joint of the coupler and dielectric tube. Additionally, in [17,18] gap-free structures are introduced to eliminate this problem. Choosing dielectric materials with high permittivity, very low loss tangent, and low secondary electron emission coefficient (SEEC) has made significant progress in decreasing the dielectric loss and multipactoring [17].…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that using materials with low secondary electron emission for the fabrication of the dielectric part or coating the inner surface of the tube can significantly reduce the multipactor loading. Also, gap-free structures are introduced to eliminate the gap between the dielectric parts of the tube and coupler at the joints known as a source of breakdown and multipactor occurrence [15][16][17]. Recently, it has been demonstrated that applying a powerful external magnetic field in the axial direction of a DLA can completely suppress the effect of multipactoring [18][19][20].…”
Section: Introductionmentioning
confidence: 99%